The Prevalence and Prognostic Significance of Frailty in Patients With Advanced Heart Failure Referred for Heart Transplantation. Issue 2 (February 2016) - Jha, Sunita R.; Hannu, Malin K.; Chang, Sungwon; Montgomery, Elyn; Harkess, Michelle; Wilhelm, Kay; Hayward, Christopher S.; Jabbour, Andrew; Spratt, Phillip M.; Newton, Phillip; Davidson, Patricia M.; Macdonald, Peter S.
Abstract : Background: Frailty is a clinically recognized syndrome of decreased physiological reserve. The heightened state of vulnerability in these patients confers a greater risk of adverse outcomes after even minor stressors. Our aim was to assess the prevalence and prognostic significance of the frailty phenotype in patients referred for heart transplantation. Methods: Consecutive patients referred or on the waiting list for heart transplantation from March 2013 underwent frailty assessment. Frailty was defined as a positive response to 3 or more of the following 5 components: weak grip strength, slowed walking speed, poor appetite, physical inactivity, and exhaustion. In addition, markers of disease severity were obtained, and all patients underwent cognitive (Montreal Cognitive Assessment) and depression (Depression in Medical Illness-10) screening. Results: One hundred twenty patients (83 men:37 women; age, 53 ± 12 years, range, 16-73 years; left ventricular ejection fraction, 27 ± 14%) underwent frailty assessment. Thirty-nine of 120 patients (33%) were assessed as frail. Frailty was associated with New York Heart Association class IV heart failure, lower body mass index, elevated intracardiac filling pressures, lower cardiac index, anemia, hypoalbuminemia, hyperbilirubinemia, cognitive impairment, and depression (all ρ < 0.05). Frailty was independent of age, sex, heart failure duration, left ventricular ejection fraction, or renal function. Frailty was an independent predictor of increased all-cause mortality: 1 year actuarial survival was 79 ± 5% in the nonfrail group compared with only 54 ± 9% for the frail group ( P < 0.005). Conclusions: Frailty is prevalent among patients with advanced symptomatic heart failure referred for heart transplantation and is associated with increased mortality. Abstract : Supplemental digital content is available in the text.